2014
DOI: 10.1016/j.addbeh.2013.08.034
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the effects of peer drinking norms on adolescents' drinker prototypes

Abstract: Background Adolescents form impressions about the type of peers who drink (i.e., drinker prototypes). The evaluation of, and perceived similarity to these prototypes are related to adolescents’ drinking. Peer drinking norms play an important role in the formation of prototypes. We experimentally examined whether manipulation of peer norms changed the evaluation of and perceived similarity to drinker prototypes and whether these changes were moderated by peers’ popularity. Methods In a pre-test, we assessed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 50 publications
4
29
0
1
Order By: Relevance
“…The PWM was designed to address the social nature of adolescent or young adult risk behaviors by acknowledging that risk behaviors are often reactions to risk-conducive environments one may encounter rather than intentionally planned behaviors (Gibbons et al 2003). The social reaction pathway of the PWM pertains to unplanned behaviors, which are posited to follow directly from behavioral willingness, which varies in part as a function of descriptive norms, but also varies according to prototypes (Blanton et al 1997; Gerrard et al 2008; Lewis et al 2016; Litt and Lewis 2016; Litt and Stock 2011; Pomery et al 2005; Teunissen et al 2014). Willingness to drink reflects openness to opportunity to drink in situations that are conducive to that behavior.…”
mentioning
confidence: 99%
“…The PWM was designed to address the social nature of adolescent or young adult risk behaviors by acknowledging that risk behaviors are often reactions to risk-conducive environments one may encounter rather than intentionally planned behaviors (Gibbons et al 2003). The social reaction pathway of the PWM pertains to unplanned behaviors, which are posited to follow directly from behavioral willingness, which varies in part as a function of descriptive norms, but also varies according to prototypes (Blanton et al 1997; Gerrard et al 2008; Lewis et al 2016; Litt and Lewis 2016; Litt and Stock 2011; Pomery et al 2005; Teunissen et al 2014). Willingness to drink reflects openness to opportunity to drink in situations that are conducive to that behavior.…”
mentioning
confidence: 99%
“…Interventions may therefore be aimed specifically at these drinker prototypes, to reduce adolescents' alcohol use. Previous research indicated that drinker prototypes are malleable (Gerrard et al, 2006;Litt & Stock, 2011;Teunissen et al, 2012;Teunissen et al, 2014), and that these adaptations in drinker prototypes can affect drinking behavior (Gerrard et al, 2006;Teunissen et al, 2012). Intervention programs could include information revealing that adolescents generally attribute negative characteristics to the type of peer that drinks heavily and positive characteristics to the type of peer that abstains.…”
Section: Discussionmentioning
confidence: 99%
“…Again, they could give their answer on a fivepoint scale, ranging from not at all to very similar. We asked these same two questions about peers who drink moderately and peers who drink heavily (Rivis et al, 2006;Rivis, Sheeran, & Armitage, 2011;Rivis & Sheeran, 2013;Teunissen et al, 2014). We provided no definition of moderate and heavy drinking, to prevent enforcing consumption levels to these prototypes that may not match participants' vision of these prototypes (Van Lettow et al, 2013).…”
Section: Drinker Prototypesmentioning
confidence: 99%
See 1 more Smart Citation
“…The consumption of ethanol is related to approximately 60 different types of diseases [1][2][3][4]. It is well known that alcohol abuse may cause acute erosive hemorrhagic gastritis, and long-term drinking could cause stomach disorders and chronic atrophic gastritis [5][6][7].…”
Section: Introductionmentioning
confidence: 99%